STRATEGI LITERASI KESEHATAN REPRODUKSI REMAJA DI PUSAT INFORMASI DAN KONSELING REMAJA MAN 1 YOGYAKARTA - Wijhati, Ellyda Rizki; Pratiwi, Maulita Listyan Eka; Nuzuliana, Rosmita (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: Reproductive health literacy is one way that can help adolescents to get information about reproductive health which is contained by PIKR in schools. The youth information and counseling center (PIKR) is a forum for activities managed from, by and for young people to provide access to information, education, counseling and services about family life planning for adolescents and other supporting activities. Objective: The purpose of this study was to determine the reproductive health literacy strategy used by Youth Information And Counseling Center MAN 1 Yogyakarta in literating students. Methods: This research method is a qualitative study conducted at MAN 1 Yogyakarta, the research informant is a BK teacher who has the duty as an advisor for PIKR and a member of PIKR in schools. Data collection techniques by interview and study documentation. The data in this study are processed inductively. Results: This research method is a qualitative study conducted at MAN 1 Yogyakarta, the research informant is a BK teacher who has the duty as an advisor for PIKR and a member of PIKR in schools. Data collection techniques by interview and study documentation. The data in this study are processed inductively. Conclusion: the most common source of reproductive health literacy referred by adolescents is internet.